THE COMPONENTS IMPACTING CUSTOMER’S BANK DETERMINATION CHOICE IN MOGADISHU, SOMALIA - Mohamed, Isse Sudi; Chowdhury, Md. Salim; Imran, Md. Al-; Imran, Md. Ali; Mimi, Afsana (Asian Finance & Banking Review, 2022)
The primary goal of this study is to concentrate on the factors influencing customer bank selection in Mogadishu, Somalia. The study’s objectives are "to investigate the role of bank image and reputation on bank selection decisions in Mogadishu, Somalia." and "to find the effect of convenience on bank selection decisions in Mogadishu, Somalia." The study used a descriptive research design with questionnaires as the primary data collection method. The sample size for this study was 80 people, with 95 bank customers as the target group. The Slovene form was used to collect the sample for this investigation. I proposed that bank marketers develop acceptable products and marketing programmes. Bank marketers should have a clear distribution of policies on specific and general techniques for persuading customers to choose a specific bank. Customers suggest some additional banking sector enhancements in addition to the services currently provided. Service quality influences bank selection decisions, as do bank image and reputation, bank reliability, and bank selection. JEL Classification Codes: D6, L1, L2, L8.